Production of linoleic acid metabolites by different probiotic strains of Lactobacillus plantarum - Aziz, Tariq; Sarwar, Abid; Al Dalali, Sam; Din, Zia Ud; Megrous, Sarah; Din, Jalal Ud; Zou, Xin; Zhennai, Yang (Progress in Nutrition, 2019)
Objective: To evaluate the capability of Lactobacillus plantarum to grow and convert polyunsaturated free fatty acids, i.e. linoleic acid (LA) into bioactive and less toxic conjugated fatty acids.  Method: Six L. plantarum strains were grown in MRS medium containing LA from 1% to 10% (w/v), and the LA metabolites formed in the medium were identified and quantitated by GC-MS. Result: In respect to the identified LA metabolites, a total of 4 metabolites were detected including linoelaidic acid, 9,12-octadecadienoic acid (Z, Z), 9,12-Octadecadienoic acid, methyl ester, and trans,trans-9,12-octadecadienoic acid, propyl ester. Among all the six L. plantarum strains, the best one was L. plantarum 2-3 which showed maximum growth and conversion of linoleic acid to different metabolites from 1% to 10 % (w/v) of LA supplied, while L. plantarum 12-5 showed maximum growth and conversion at higher concentration of LA supplied and showed minimal growth and conversion at lower concentration of LA. Conclusion: Among all the six L. plantarum strains, the best one was L. plantarum 2-3 which showed maximum growth and conversion of LA to different metabolites.